Analisis Pelayanan Dan Strategi Manajemen Sumber Daya Manusia Pada Pelanggan Travel Haji Dan Umroh Arminareka Perdana Cabang Namlea Kab. Buru Tahun 2022 - Ramli, Sahla; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research aims to describe human resource management strategies in Hajj and Umrah services at Arminareka Perdana travel. This research uses a quantitative approach using explanatory research methods. The population in this study was 123 Hajj and Umrah pilgrims from Travel Arminareka Perdana Branch, Namlea District. Buru in 2022. With calculations using the Slovin formula, a sample of 55 respondents was obtained. To solve the problems in this research, SPSS was used to analyze, normality test, classical assumption test, hypothesis test, multiple linear regression test and customized R² coefficient test. The results of this research simultaneously and partially service and HR strategy have a significant effect on customer satisfaction. Keywords: Service, HR Strategy, Customer Satisfaction